Efficacy of electroacupuncture using “Jin’s three needles” points on postoperative urinary retention after spinal anesthesia - Le, Cong Hau; Nguyen, Thi Tan; Doan, Thi Nhat Le; Phan, Hai Thanh (Tạp chí Y Dược Huế, 2025)
Background: There is still a lack of high-quality clinical evidence to explore the effect of electroacupuncture using “Jin’s Three Needles” in patients with postoperative urinary retention (POUR) after spinal anesthesia. Objectives: To assess the clinical therapeutic effect of “Jin’s Three Needles” electroacupuncture on POUR after spinal anesthesia, and to identify some treatment-related factors influencing efficacy. Methods: Thirty-one patients diagnosed with postoperative urinary retention after spinal anesthesia in the Center of Orthopedic and Plastic Surgery - Hue Central Hospital from June 2022 to June 2024 were included using a convenience sampling method (non-probability sampling). Results: The average age of the participants was 73.03 ± 20.84 years, with participants aged 50 years and older accounting for 83.87%. The male-to-female ratio was 9/22. The average surgical duration was 70.81 ± 16.23 minutes. The distance from the bladder dome to the superior border of the pubic symphysis was mainly ≤ 5 centimeters. Electroacupuncture using “Jin’s Three Needles” to treat postoperative urinary retention after spinal anesthesia showed very good and good effectiveness of 93.55%. No treatment failures were recorded. Treatment-related factors influencing efficacy consist of age and distance from the bladder dome to the superior border of the pubic symphysis (p > 0.05). Conclusion: This study can provide more comprehensive evidence to prove whether electroacupuncture using “Jin’s Three Needles” is effective for patients with POUR after spinal anesthesia and identify some treatment-related factors influencing efficacy.